A review of riverbank and coastal erosion protection structure - Md. Nasir, Muhamad Nadjmi; Tuan Ismail, Tuan Noor Hasanah; Yahya, Nur Faezah; Yusop, Fatimah Mohamed; Adnan, Suraya Hani; Abdullah, Nor Maizzaty; Mat Hassan, Nik Normunira (Penerbit UTHM, 2022)
Riverbank and coastal erosion are not new issues; it has been occurring globally for a long time. They are the most critical and unpredictable hazard issue, causing the loss of valuable property and land, posing a threat to the closest residents and having an economic impact. This review paper discusses the causes and consequences of riverbank and coastal erosion, and the dominant erosion processes involved. This paper further reviews the effectiveness of the protection method that was successfully being used to protect riverbank and coastal against repeated erosional attacks in Malaysia and its limitations. The last part of this paper reviews the potential of geobag as a rapid protection structure to the riverbank and coastal erosion. This method could prove to be an alternative to traditional rock-fill methods or bioengineering techniques, which are often quite complex and costly.